Peningkatan Nalar Kritis Pembelajaran PAKat Melalui Model PBL Berbantuan E-Modul Siswa Fase D Kelas VII di SMPN 26 Surakarta - Yohanes Adventus David Kristian (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Abstract. The implementation of the Merdeka curriculum at SMPN 26 began with choosing an independent type of change and in the future it will lead to independent sharing. Catholic Religious Education participates to strive for this. Based on the diagnostic assessment, the critical thinking of seventh grade Catholic students is still minimal, characterized by low literacy scores in the education report card and the inability of students to answer C3-C6 questions. So a class action research was conducted to improve the critical reasoning ability of seventh grade students by applying a relevant model, namely Problem Based Learning assisted by E-Modules. The research was carried out with the type of action research on a sample of 11 seventh grade students who were Catholic on October 24 and November 2 with 2 cycles in 4 stages. The results of the research in cycle 1 obtained data on the ability to reason critically VII grade students reached 67% and increased 18% in cycle 2 by 85%, with an increase in criteria from feasible and capable to proficient from 36% to 83% while for learning outcomes there was an increase from 82% to 100% achievement of KKTP, with an increase in criteria from feasible and capable to proficient from 36% to 83%. From the results of this study, it can be concluded that the Problem Based Learning learning model assisted by E-Modules is effective in improving critical thinking skills and learning outcomes of seventh grade students at SMPN 26 Surakarta.